A new cascade halosulfonylation of 1, 7-enynes toward 3, 4-dihydroquinolin-2(1H)-ones via sulfonyl radical-triggered addition/6-exo-dig cyclization. Issue 9 (17th December 2015) - Zhu, Yi-Long; Jiang, Bo; Hao, Wen-Juan; Wang, Ai-Fang; Qiu, Jiang-Kai; Wei, Ping; Wang, De-Cai; Li, Guigen; Tu, Shu-Jiang
Abstract : A new cascade three-component halosulfonylation of 1, 7-enynes for efficient synthesis of densely functionalized 3, 4-dihydroquinolin-2(1 H )-ones has been established from readily accessible arylsulfonyl hydrazides and NIS (or NBS). Abstract : A new cascade three-component halosulfonylation of 1, 7-enynes for efficient synthesis of densely functionalized 3, 4-dihydroquinolin-2(1 H )-ones has been established from readily accessible arylsulfonyl hydrazides and NIS (or NBS). The reaction pathway involves in situ -generated sulfonyl radical-triggered α, β-conjugated addition/6- exo-dig cyclization/radical coupling sequence, resulting in continuous multiple bond-forming events including C–S, C–C and C–I (or C–Br) bonds to rapidly build up molecular complexity.